World stock market and Kazakhstan (Journal of Economic Research & Business Administration, 2015)
The problem of world stock market and Kazakhstan. Based on the analysis of existing economic – legal approaches to government support and regulation of the stock market of Kazakhstan, foreign experience developed measures to further improve it. The globalization of world economic relations form the global stock market is a mechanism of financial resources in ac-cordance with supply and demand in the global capital markets. Kazakhstan's stock market in size, in relation to the the country's economy is small, its liquidity remains low. Depending on the power of external causes (International money) stock market priced in Emergency Situations. 2007-2008, it was noted that the global financial inflation directly and adversely affected the Kazakh stock market. The purpose of the study is to develop mechanisms to control risk in the stock market in crisis. Methodology of the work contains a conceptual approach based on system review of the risk management of the stock market. Findings research may be applied in the development of program materials development of the stock market.
Keywords: Action; exchange; capitalization; «People's IPO»; stock exchange; security